2020
DOI: 10.1007/s00167-020-06170-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased hip arthroscopy operative duration is an independent risk factor for overnight hospital admission

Abstract: PurposeThe purpose of this study was to determine the association between operative duration and short‐term complications as well as overnight hospital admission following hip arthroscopy. MethodsHip arthroscopy cases from 2006 to 2016 were retrieved from the National Surgical Quality Improvement Program registry, which prospectively collects 30‐day postoperative complications. Patients were stratified into the following groups based on procedure length: group 1 (< 60 min), group 2 (60–120 min), and group 3 (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…8 On the other hand, Bovonratwet et al focused specifically on overnight admission after hip arthroscopy and concluded that operative time of 60-120 min was an independent risk factor for overnight hospital admission. 9 The authors reported an overall readmission rate of 14%, which is comparable to the 9% overnight admission rate from the present study. The findings of our study concur with Bovonratwet et al: Increased operative time was a strong positive predictor of overnight hospital admission after outpatient hip arthroscopy.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…8 On the other hand, Bovonratwet et al focused specifically on overnight admission after hip arthroscopy and concluded that operative time of 60-120 min was an independent risk factor for overnight hospital admission. 9 The authors reported an overall readmission rate of 14%, which is comparable to the 9% overnight admission rate from the present study. The findings of our study concur with Bovonratwet et al: Increased operative time was a strong positive predictor of overnight hospital admission after outpatient hip arthroscopy.…”
Section: Discussionsupporting
confidence: 84%
“…Several investigations have used conventional statistical modeling to determine risk factors for inpatient admission after hip arthroscopy. 8,9,21,22 Du et al identified 1,931 patients who underwent hip arthroscopy and the rate of 30-day readmission following index procedure was estimated to be 0.9%. 8 Multivariate analysis identified increasing BMI, chronic corticosteroid use, and perioperative blood transfusions as independent risk factors associated with unplanned admission within 30 days after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations